ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di BEI Periode Tahun 2014-2016) - Tixvi Yuly Andryastanty, 14.05.52.0286; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2018)
This research aims to examine the effect of profitability, asset structure, firm size, business risk, and liquidity to capital structure at manufacturing companies listed on the Indonesian Stock Exchange (Bursa Efek Indonesia) in 2014-2016.The population in this research are Manufacturing Companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia). Sampling method using purposive sampling in the technique of data analysis is multiple linear regression analysis.The results of this research indicate that Profitability and Business Risk have a negative influence on Capital Structure while Asset Structure, Asset Growth, Company Size, and Liquidity have positive effect on Capital Structure. Keywords: Profitability, Asset Structure, Company Size, Business Risk, and Liquidity, Capital Structure.